Multi-level SMA/lead rubber bearing isolation system for seismic protection of bridges - Cao, Sasa; Ozbulut, Osman E; Wu, Suiwen; Sun, Zhuo; Deng, Jiangdong (Smart materials and structures, 2020)
In performance-based seismic design, bridges are expected to satisfy specific performance objectives under several levels of seismic hazard. In this paper, a multi-level SMA/lead rubber bearing (ML-SLRB) isolation system was proposed to ensure both isolation efficiency and capability to limit excessive bearing displacements under different levels of earthquake excitations. The ML-SLRBs also offer advantages such as the ability to provide re-centering forces and good fatigue and corrosion-resistant. The ML-SLRB isolation system consists of three groups of SMA cables, each is designed to be activated at a certain seismic hazard level, and a conventional lead rubber bearing. First, the design and working mechanism of this new isolation system were described in detail. Then, a design procedure was proposed for seismic isolation of bridge structures with ML-SLRBs. Next, the hysteretic response of ML-SLRBs was simulated in a general-purpose structural engineering software. A four-span continuous box-girder bridge was designed and modeled with different isolation systems including ML-SLRBs. Nonlinear dynamic analyses of the isolated bridges were conducted under both far-fault and near-fault earthquakes. Results show that compared to isolations systems that do not adapt their stiffness according to increasing seismic demand, e.g. the isolators with a bilinear force-displacement response, the proposed isolation system exhibits high isolation efficiency at small or moderate earthquakes, while effectively limits the bridge displacements to avoid pounding and girder unseating under extreme earthquakes.